Description of the immature stages of Notalina morsei Holzenthal, 1986 (Trichoptera: Leptoceridae) and an updated key to larvae of Neotropical Leptoceridae genera - Calor, Adolfo R.; Froehlich, Claudio G. (Zootaxa, 2008)
The endemic Neotropical long-horned caddisfly subgenus Notalina (Neonotalina) Holzenthal contains nine described species, but its immature stages are unknown. In this paper the larvae and pupae of Notalina morsei Holzenthal 1986 from southeastern Brazil are described and illustrated. Larvae of the subgenus are easily recognized from other Neotropical leptocerids by the following characters: ventral apotome which is broad anteriorly and narrow posteriorly; the metanotum with three sclerites; the metasternum bearing 10–12 setae; the gill arrangement, usually including ventral and dorsal filaments from abdominal segments II to VI; and abdominal tergite IX with 6 long and 4 short setae. An updated key to known larvae of Neotropical Leptoceridae genera is provided.